THE ACQUISITION OF VERB PHRASES INDICATED IN EFL STUDENTS RECOUNT TEXT - Astuti Pratiwi Ramadhani; Muhammad Khairi Ikhsan (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
This study aims to investigate the interlanguage in regard to verb phrase acquisition that high school students produce when they write English especially recount text. This study is conducted on the basis of the fact that high achiever students still make errors although they have learned English for a long time. Also, the error themselves are as a system and can be used to determine interlanguage. The result showed that around 40% students produce error in producing writing text. It means most students produce correct structure in their sentence. However, students mostly have problem in acquiring gerunds, modals, and negative transformation of verb phrase. Also, not many students used passive transformation in their writing text. Many of them prefer to use active sentences rather than passive one. In addition, there are three processes that contribute to students’ interlanguage; language transfer, transfers of training, and overgeneralization. The errors they make show that they go through development process and their acquisition of the target language must be on the interlanguage continuum. Therefore, interlanguage provides a more comprehensive way dealing with students’ error, they are not perceived as something negative but as a construction of their own process of learning.